Avaliação de políticas públicas para mulheres violentadas: a contribuição das notificações de violência interpessoal, no âmbito da saúde, de 2013 a 2022, no estado do Ceará - Leal, Layane Maria (2024)
The general objective of this research is to evaluate how notifications of interpersonal violence, used in the public health system, contribute to coping with violence against women in the State of Ceará. Thus, it is understood that this phenomenon is the result of a socio-historical and cultural construction, based on gender inequality, patriarchy and machismo, a context that demands responses from the public authorities through various policies that are part of the care network, including health. In this sense, the specific objectives are: to identify the socioeconomic profile of the abused women; to investigate the characteristics of events of violence against women in the State of Ceará; to analyze the social markers of inequality present in the context of violence against women from the perspective of intersectionality. In order to meet these objectives, an evaluation was carried out based on the experiential approach of Lejano (2012). According to the author, the evaluator must integrate multiple knowledges, observing the relationship between their norms (text) and the context where the actions are performed in daily life. Methodologically, the present study is qualitative in nature, has an exploratory and descriptive purpose. Regarding data collection, a bibliographic survey and documentary research were carried out. Content analysis was adopted as a method of data analysis. From the analyses carried out, it was observed that the violence perpetrated against women is crossed by multiple expressions of the social and public health issue. The results presented indicate that compulsory notification is an important tool for coping with violence, since it contributes to the understanding of the phenomenon through the epidemiological survey of the situation, as well as to foster the construction of public policies aimed at this theme.